Congenital Brain Tumor within the First 2 Months of Life - Masaya Sugimoto; Clara Kurishima; Satoshi Masutani; Masanori Tamura; Hideaki Senzaki (Elsevier, 2015)
Congenital brain tumors (CBTs), defined as tumors presenting within 60 days after birth, are extremely rare and account for only 0.5-1.9% of all pediatric brain tumors. Teratoma is the most common type of CBT, although there are many other poorly described forms. Prenatal diagnosis of CBT is often difficult and usually based on clinical characteristics and radiological findings with magnetic resonance imaging and ultrasonography. The prognosis of patients with CBT depends on the histopathological features of the tumor and its location. Even after several investigations have been performed, a clear direction for diagnosis and treatment of fetal intracranial tumors is still lacking. Further studies are thus needed to clarify its clinical characteristics and establish recommendations for management.